INNOVATE Research: Impact of a workshop to develop researcher capacity to engage youth in research. (9th September 2020) - Hawke, Lisa D.; Darnay, Karleigh; Brown, Marion; Iyer, Srividya; Ben‐David, Shelly; Khaleghi‐Moghaddam, Mohammad; Relihan, Jacqueline; Barbic, Skye; Lachance, Lisa; Mathias, Steve; Halsall, Tanya; Kidd, Sean A.; et al.
Abstract: Background: Engaging youth in research provides substantial benefits to research about youth‐related needs, concerns and interventions. However, researchers require training and capacity development to work in this manner. Methods: A capacity‐building intervention, INNOVATE Research, was co‐designed with youth and adult researchers and delivered to researchers in three major academic research institutions across Canada. Fifty‐seven attendees participated in this research project evaluating youth engagement practices, attitudes, perceived barriers, and perceived capacity development needs before attending the intervention and six months later. Results: The intervention attracted researchers across various career levels, roles and disciplines. Participants were highly satisfied with the workshop activities. Follow‐up assessments revealed significant increases in self‐efficacy six months after the workshop ( P  = .035). Among possible barriers to youth engagement, four barriers significantly declined at follow‐up. The barriers that decreased were largely related to practical knowledge about how to engage youth in research. Significantly more participants had integrated youth engagement into their teaching activities six months after the workshop compared to those who were doing so before the workshop ( P  = .007). A large proportion (71.9%) of participants expressed the need for a strengthened network of youth‐engaged researchers; other future capacity‐building approaches were also endorsed. Conclusions: The INNOVATE Research project provided improvements in youth engagement attitudes and practices among researchers, while lifting barriers. Future capacity‐building work should continue to enhance the capacity of researchers to engage youth in research. Researchers notably pointed to the need to establish a network of youth‐engaged researchers to provide ongoing, sustainable gains in youth engagement.